Review Article about the Role of Bacteria in Cadmium Bioremediation - Hussein Khudhair Hussein Abd Sultani; Sajad Hassan Hadi Mohsen; Ibrahim Samir Abdul Sattar Abdullah (American Journal of Biology and Natural Sciences, 2025)
Elevated levels of cadmium in soils and irrigation water pose a risk to food safety, human and animal health, and the environment. Because microorganisms, particularly bacteria, have a proven capacity to retain and convert heavy metals, microbial bioremediation has emerged as a promising approach to lower the concentration of toxic chemicals in the environment. Understanding the role of bacteria in cadmium bioremediation is crucial for developing effective strategies to remediate cadmium-contaminated environments. This paper aims to explore the intricate relationship between bacteria and cadmium, focusing on the various mechanisms employed by bacteria to resist and tolerate cadmium, and provide insights into how bacteria can be harnessed for efficient cadmium removal.